Optimisasi Rute Pengiriman Produk Usaha Mikro Kecil dan Menengah Menggunakan Metode Metaheuristik Particle Swarm Optimization - Meitasari, Nur Annisa Venny; Adhi, Antono (Jurnal Serambi Engineering, 2025)
This study aims to optimise the delivery routes of Cripang Bu Fitri, a Small and Medium Enterprise (SME) in Semarang City, using the Particle Swarm Optimization (PSO) metaheuristic method. The main problem is the high demand from partners and the use of intuitive routes by salesmen, resulting in inefficient travel distances and operational costs. This study applies PSO to solve the Traveling Salesman Problem (TSP), focusing on reducing delivery distance and time. The data obtained was processed using the Visual Basic 6.0 application. The results of the PSO calculations show that the newly generated route is more efficient than the original route. The total distance for the new route is 100550 metres compared to 115950 metres for the original route, resulting in a 13% improvement in efficiency. This result highlights the effectiveness of PSO in reducing operational costs and delivery times, thereby improving the competitiveness of SMEs. The use of this method is recommended for logistics optimisation in other SME sectors.